2011
DOI: 10.1186/1757-7241-19-38
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Cerebral Performance Category to classify neurological status among survivors of ventricular fibrillation arrest: a cohort study

Abstract: Background: The Cerebral Performance Category (CPC) score is widely used in research and quality assurance to assess neurologic outcome following cardiac arrest. However, little is known about the inter-and intra-reviewer reliability of the CPC. Methods:We undertook an investigation to assess the inter-reviewer and source document reliability of the CPC among a cohort of survivors from out-of-hospital ventricular fibrillation cardiac arrest (n = 131) in a large metropolitan area between November 1, 2003 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 14 publications
0
92
0
3
Order By: Relevance
“…7,8,10,13,14,43,44 Among the strengths of the present study are the high inclusion ratio and the fact that we were able to obtain information on patients who chose not to participate in the study but consented to the main trial. These data were used to perform multiple imputations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,10,13,14,43,44 Among the strengths of the present study are the high inclusion ratio and the fact that we were able to obtain information on patients who chose not to participate in the study but consented to the main trial. These data were used to perform multiple imputations.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Despite a good outcome according to the CPC, cognitive difficulties may be prevalent as reported in several smaller studies using neuropsychological tests. 9,10 In a recent review, 30% to 50% of survivors after cardiac arrest were reported to suffer from cognitive impairment.…”
Section: Clinical Perspective On P 1349mentioning
confidence: 99%
“…If possible, cerebral performance category (CPC) was additionally assessed 6 months after CPR. For statistical analyses a CPC score of 1 and 2 was considered to be a favorable neurological outcome whereas CPC 3 to 5 was classified as an unfavorable status (21).…”
Section: Methodsmentioning
confidence: 99%
“…On this point, considering the lack of a systematic precise neurological evaluation, either a neurologist's examination or a standardized neurological rating sheet would be useful. For instance, the ILCOR recommends the Cerebral Performance Category scale, although this scale is subject to an inter-and intra-reviewer variability [10,15] .…”
Section: Discussionmentioning
confidence: 99%